Maternal Melatonin Therapy Rescues Prenatal Dexamethasone and Postnatal High-Fat Diet Induced Programmed Hypertension in Male Rat Offspring - Tain, You-Lin; Sheen, Jiunn-Ming; Yu, Hong-Ren; Chen, Chih-Cheng; Tiao, Mao-Meng; Hsu, Chien-Ning; Lin, Yu-Ju; Kuo, Kuang-Che; Huang, Li-Tung (Frontiers in Physiology, 2015)
Prenatal dexamethasone (DEX) exposure and high-fat (HF) intake are linked to hypertension. We examined whether maternal melatonin therapy prevents programmed hypertension synergistically induced by prenatal DEX plus postnatal HF in adult offspring. We also examined whether DEX and melatonin causes renal programming using next-generation RNA sequencing (NGS) technology. Pregnant Sprague-Dawley rats received intraperitoneal dexamethasone (0.1 mg/kg) or vehicle from gestational day 16 to 22. In the melatonin-treatment groups (M), rats received 0.01% melatonin in drinking water during their entire pregnancy and lactation. Male offspring were assigned to five groups: control, DEX, HF, DEX+HF, and DEX+HF+M. Male offspring in the HF group were fed a HF diet from weaning to 4 months of age. Prenatal DEX and postnatal HF diet synergistically induced programmed hypertension in adult offspring, which melatonin prevented. Maternal melatonin treatment modified over 3000 renal transcripts in the developing offspring kidney. Our NGS data indicate that PPAR signaling and fatty acid metabolism are two significantly regulated pathways. In addition, maternal melatonin therapy elicits longstanding alterations on renal programming, including regulation of the melatonin signaling pathway and upregulation of Agtr1b and Mas1 expression in the renin-angiotensin system (RAS), to protect male offspring against programmed hypertension. Postnatal HF aggravates prenatal DEX induced programmed hypertension in adult offspring, which melatonin prevented. The protective effects of melatonin on programmed hypertension is associated with regulation of the RAS and melatonin receptors. The long-term effects of maternal melatonin therapy on renal transcriptome require further clarification.